Influence of cryogenic treatment on mechanical performance of friction stir Al-Zn-Cu alloy weldments. (August 2020) - Bansal, Anuj; Singla, Anil Kumar; Dwivedi, Vinay; Goyal, Deepak Kumar; Singla, Jonny; Gupta, Munish Kumar; Krolczyk, Grzegorz M.
Highlights: Refinement of grains was observed in the NZ of FSW Al7050-T7451 weldments, after exposure to cryogenic temperature (88 K). Augmentation in microhardness was noticed for cryo-treated FSW weldments attributable to refinement of grains. Deep cryogenic treatment (DCT) has caused notable improvement in impact toughness, yield strength and % elongation of FSW weldments. Abstract: Al-Zn-Cu alloy Al7050-T7451 is used extensively in the aero-space industries. Aerospace components are generally joined using riveting, which increases the overall weight of aeroplane. In this context, friction stir welding (FSW) process could be a potential solution. In this research work, Al7050-T7451 specimens were welded by FSW, using different parametric combinations of tool rotation and welding speed. The friction-stir weldments were further subjected to deep cryogenic treatment. Microstructure and some mechanical properties of the weldments were investigated for both cryo-treated and untreated conditions. It was observed that the grain size of the nugget zone (NZ) got refined after the cryogenic treatment. It was also revealed that microhardness was more in case of cryo-treated joints as compared to untreated. Micro-hardness of the NZ was observed to be highest due to formation of finer grains after exposure to cryogenic temperature. Deep cryogenic treatment has also improved impact toughness and tensile properties such as yield strength and % elongation of the FSW joints.